Drug Delivery: Engineering Extracellular Vesicles with the Tools of Enzyme Prodrug Therapy (Adv. Mater. 15/2018). Issue 15 (14th April 2018) - Fuhrmann, Gregor; Chandrawati, Rona; Parmar, Paresh A.; Keane, Timothy J.; Maynard, Stephanie A.; Bertazzo, Sergio; Stevens, Molly M.
Abstract : In article number1706616, Molly M. Stevens and co‐workers present the incorporation of extracellular vesicles into biocompatible poly(vinyl alcohol)‐based hydrogels to advance the concept of enzyme‐prodrug therapy. Hydrogels are imaged by density‐dependent color scanning electron microscopy taking advantage of the backscattered signal of the labeled vesicles. The vesicles appear as bright red dots within the hydrogel matrix, indicating densitydependent microscopy as a powerful tool for the spatial analysis of vesicle distribution and localization in 3D.